Singlet oxygen, flavonols and photoinhibition in green and senescing silver birch leaves - Mattila Heta; Sotoudehnia Pooneh; Kuuslampi Telma; Stracke Ralf; Mishra Kumud B.; Tyystjärvi Esa (SPRINGER HEIDELBERG, 2025)
During autumn senescence, deciduous trees degrade chlorophyll and may synthesize flavonols. We measured photosynthetic parameters, epidermal flavonols, singlet oxygen production in vivo and photoinhibition of the photosystems (PSII and PSI) from green and senescing silver birch (Betula pendula) leaves. Chlorophyll a fluorescence and P700 absorbance measurements showed that the amounts of both photosystems decreased throughout autumn senescence, but the remaining PSII units stayed functional until ~ 90% of leaf chlorophyll was degraded. An increase in the chlorophyll a to b ratio, a decrease in > 700 nm absorbance and a blue shift of the PSI fluorescence peak at 77 K suggest that light-harvesting complex I was first degraded during senescence, followed by light-harvesting complex II and finally the photosystems. Senescing leaves produced more singlet oxygen than green leaves, possibly because low light absorption by senescing leaves allows high flux of incident light per photosystem. Senescing leaves also induced less non-photochemical quenching, which may contribute to increased singlet oxygen production. Faster photoinhibition of both photosystems in senescing than in green leaves, under high light, was most probably caused by low absorption of light and rapid singlet oxygen production. However, senescing leaves maintained the capacity to recover from photoinhibition of PSII. Amounts of epidermal flavonols and singlet oxygen correlated neither in green nor in senescing leaves of silver birch. Moreover, Arabidopsis thaliana mutants, incapable of synthesizing flavonols, were not more susceptible to photoinhibition of PSII or PSI than wild type plants; screening of chlorophyll absorption by flavonols was, however, small in A. thaliana. These results suggest that flavonols do not protect against photoinhibition or singlet oxygen production in chloroplasts.